Innovative Approaches for Onychomycosis Treatment: An Insight Into Natural Remedies and Novel Pharmaceutical Formulations - Chopra, Hitesh; Munjal, Kavita; Goyal, Rajat; Wilson, Kashish; Dhama, Kuldeep (Scripta Medica, 2024)
Onychomycosis, commonly referred to as nail fungus, is a persistent and difficult-to-treat condition that affects both toes and fingernails. Even though traditional treatments such as antifungal medications and topical ointments are effective in some cases, they are often associated with significant side effects and a high recurrence rate. There has been a growing interest in alternative and complementary treatments in recent years, including natural remedies and new pharmaceutical formulations, which are becoming increasingly popular. This review aims to explore the current state of knowledge surrounding onychomycosis treatment and its challenges, with a particular focus on the benefits and limitations of the current therapeutic options. Also, light is shed on the prospects available as treatment options.